Determinan kepuasan pelanggan: Studi empiris pada penginapan Syariah Asri Jakarta - Akhmadi, Ali (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2025)
This study aims to analyze the influence of service quality, price, and brand image on customer satisfaction at Penginepan Syariah Asri Jakarta.This research employs a quantitative approach using primary data collected through a Likert-scale questionnaire. The population of this study consists of all customers of Penginepan Syariah Asri Jakarta. The sampling technique used was non-probability sampling, with a margin of error formula, yielding a sample of 97 respondents. Data analysis was conducted using SPSS version 26, including validity and reliability tests, partial tests (T-tests), and coefficient-of-determination tests. The analysis results indicate that, partially, service quality, price, and brand image each have a significant influence on customer satisfaction at Penginepan Syariah Asri Jakarta. This study provides an empirical contribution to the services marketing literature, particularly within the context of the under-researched sharia hospitality industry in Indonesia, by simultaneously testing three key determinants of customer satisfaction.